CHRONIC SLEEP DEPRIVATION – ITS IMPACT AND RISK OF METABOLIC AND NEURODEGENERATIVE DISORDERS: A LITERATURE REVIEW - Kondracki, Patryk; Rodziewicz, Jakub; Daniszewski, Wiktor; Kretschmer, Viktoria; Sobolewska, Ewa; Baranowska, Magdalena; Markowski, Daniel (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and Purpose: Sleep plays a key role in maintaining physiological homeostasis, influencing not only cognitive functions but also the regulation of metabolic and immune processes. The modern lifestyle significantly contributes to reduced sleep duration and quality. Chronic sleep deprivation is becoming a widespread public health issue. The aim of this study is to review current scientific literature on the effects of chronic sleep deprivation on metabolism and to assess its role in the pathogenesis of metabolic and neurodegenerative diseases. Brief Description of the State of Knowledge: A growing body of research indicates that chronic sleep deficits are associated with dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis, disturbances in glucose-insulin metabolism, and alterations in the secretion of appetite-regulating hormones. These consequences promote the development of insulin resistance, obesity, type 2 diabetes, and metabolic syndrome. Moreover, increasing evidence links chronic sleep deprivation to heightened neuroinflammatory processes and the accumulation of pathological proteins in the central nervous system, raising the risk of neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Conclusions: In recent decades, insufficient sleep has become a global issue affecting people of all age groups. There is growing evidence supporting the association between chronic sleep deprivation and the development of chronic diseases, as well as a shortened life expectancy. Enhancing transparency in reporting and improving public access to data on the consequences of sleep deprivation are essential for protecting public health.